Misvaluation and the Asset Growth Anomaly - Lambertides, Neophytos (My University, 2022)
It is widely shown that stocks with higher asset growth paradoxically earn lower returns (hereafter, the asset growth anomaly). Studies have pointed towards errors in expectations, over-investment and limits-to-arbitrage as potential causes of misvaluation, the most documented explanation of the asset growth anomaly. What studies have not yet done, however, is provide compelling evidence that mispricing is the cause of the anomaly. Using a multiples valuation approach to calculate a direct proxy of mispricing (i.e., a firm-specific misvaluation level relative to peers), this study shows that the negative relation between asset growth and subsequent returns occurs in undervalued stocks, whereas it is absent in overvalued stocks. By comparing and contrasting the theories on real options and asset pricing, the findings suggest that the asset growth anomaly is driven by the real options component, particularly for undervalued firms. The findings therefore provide new evidence in the mispricing-based hypothesis for the asset growth anomaly.
Keywords: Asset growth anomaly; Asset pricing; Mispricing; Misvaluation; Real Options; Stock market anomalies; Stock returns